Education on the Knowledge of Youth about Youth Care Health Services (PKPR) - Sartika, Andry; Oktarianita, Oktarianita; Padila, Padila; Andri, Juli; Andrianto, Muhammad Bagus (JOSING: Journal of Nursing and Health, 2021)
This study aims to determine the effect of counseling on adolescent knowledge about Youth Care Health Services (PKPR) at the Bintang Terampil Orphanage, Bengkulu City. This type of research is quantitative research conducted at the Bintang Terampil Orphanage, Bengkulu City. The population observed was all 30 adolescents in the Bintang Skilled Orphanage, Bengkulu City, with a total sampling technique of selecting samples. Data collection was carried out by distributing questionnaires containing questions to adolescents about PKPR twice to determine their pretest and posttest knowledge about PKPR. Information was obtained in the univariate and bivariate test analysis. The results showed that the average knowledge score before counseling was 8.57, and after counseling was 12.13. Adolescents' knowledge about PKPR before and after counseling was a mean value of 3.567, a standard deviation of 2.208, with a p-value of 0.005. In conclusion, there are differences in adolescent knowledge about PKPR before and after counseling. Keywords: Adolescent Knowledge, Counseling, PKPR